Telepsychology for psychotherapists: lessons learned in times of Covid-19 - Rojas Jara, Claudio; Polanco-Carrasco, Roberto; Caycho-Rodríguez, Tomás; Muñoz-Vega, Catalina; Muñoz-Marabolí, Mariela; Luna-Gómez, Tamara; Muñoz-Torres, Tamara (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
The necessary health measures proposed to mitigate the viral spread of SARS-CoV-2, such as physical distancing and quarantines, have had an impact not only on the mental health of the population but have also forced changes in the provision of psychological services. The present study aims to gather essential information on the concept, advantages, disadvantages, uses and recommendations of telepsychology in times of COVID-19. To this end, a systematic review of the scientific evidence available in the Scopus, PubMed and Web of Science databases was carried out. Among the results, accessibility, reduction of stigma and flexibility in its application are highlighted. Limitations such as insecurity of data privacy, access barriers and low clinical training in the competencies required for this format are also mentioned. On the other hand, favorable evidence was found for its use in the treatment of post-traumatic stress disorder, panic and agoraphobia, generalized anxiety, and trauma. It is concluded that psychotherapeutic intervention through telepsychology, in consideration of certain recommendations and critical suggestions, can offer satisfactory results for the patient and therapist and be suitable for various age ranges and disorders.